Corporate social responsibility and accounting conservatism. (15th November 2019) - Hong, Soonwook
This study aims to clarify the relationship between sustainability management and accounting conservatism. Perspectives on sustainability management are diverse, including positive, negative, and neutral perspectives. It is worth studying sustainability management given that it has not reached a consensus. This study analyses sustainability management using ESG rating provided by KCGS as a proxy variable of sustainability management for the listed companies in Korea Exchange from 2010 to 2016. The result demonstrates that the higher the ESG rating, the lower the conservatism. The contribution of this paper is to verify the relationship between sustainability management and conservatism of Korean companies which have not been done recently. In addition, there is an implication in that it provided a starting point for the utilisation of the ESG ratings announced by KCGS.